The relationship between anxiety and salivary alpha amylase levels in mothers of neonates admitted to neonatal intensive care unit : anxiety and salivary alpha amylase levels in mothers - eghbalian, fateme; Ahmadpanah , Mohammad; Seif Rabiei , Mohammad Ali; Khadem, Parya; Saati Asr, Mohammad Hasan (Iranian Journal of Child Neurology, 2023)
Objectives Anxiety is a significant health issue in mothers who give birth to unhealthy neonates. Different studies have investigated the relationship between anxiety and alpha-amylase. According to the necessity for psychological care of mothers whose infants are hospitalized in intensive care units and consequently the anxiety that is imposed on mothers due to the condition, this study aims to assess anxiety in these mothers and the relationship between this anxiety and salivary alpha-amylase. Materials & Methods This study was a cross-sectional study conducted at Besat Hospital in Hamadan in 2021. Thirty mothers were enrolled in the study through a census method sampling. The Hamilton questionnaire measured maternal anxiety during the children’s hospitalization period. Salivary alpha-amylase samples were taken from all mothers according to the scientific method, and mothers’ salivary alphaamylase levels were measured. All the gathered data were analyzed using SPSS 21 software. The significant level was considered 0.05 in all comparisons. Results The mean age of the 30 mothers was 29.27+6.24 years. The mean score of maternal anxiety was 16.27 + 6.78, and the mean salivary amylase level was 33.02 ± 16.22 U / ml. Fourteen mothers obtained low anxiety scores, 14 had moderate anxiety, and two had severe anxiety. No significant relationship was found between the mean of salivary alpha-amylase at the three levels and anxiety. There was no significant relationship between anxiety level with parent location,age, mother’s level of education, infant gender, and child rank. Conclusion According to the results of the present study, there was no significant relationship between the level of alpha-amylase and the level of anxiety in mothers of neonates admitted to the neonatal intensive care unit (NICU), so further researches in similar groups that are in anxious conditions seem necessary.